Transição para economia colaborativa: novas oportunidades de negócios de design autoral - Lopes, Gabriela Catarina Martini de Vargas (2018)
This research set out to describe the main drivers and obstacles of the sharing relationships between the actors in the collaborative authoring design fairs. A multicase study focused on authoring design as innovation that envisioned collaborative fairs as a new business opportunity. The analysis takes place under the lens of the sociotechnical transition theory with the Multilevel Analysis Perspective (PMN) based on the theory of sustainable development of the circular and shared economies. Through a qualitative research, the data collected through a semi-structured interview, applied to the exhibitors and organizers during the second half of 2018, showed that it can be said that the author design fairs are collaborative, since the actors involved are motivated by the opportunity of sustainable development. It was also possible to see that the obstacles that drive the drivers of developing innovative solutions for the transition to sustainability encompass the three pillars of sustainable economic, environmental and social development.